2016
DOI: 10.1016/j.jbmt.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing an instrument to assess aquaticity in humans

Abstract: We developed and validated an aquaticity assessment test (AAT) for the evaluation of human physical adequacy in the water. Forty-six volunteers (25M/21F; 20±8 years,) participated and performed 10 easy-to-administer and practical aquatic tasks. Group A was formed by 36 elite athletes (M/F 20/16, 24.7±10yrs) from two sports categories depending on their affinity to the water environment: terrestrial (wrestling, cycling, dancing) and aquatic (swimming, synchronized swimming, free diving) sports. Group B was form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Furthermore, our results showed that the total score of the aquaticity testing protocol is reliable for the evaluation of students’ aquaticity (ICC = 0.98; SEM = 0.54 AU; SEM% = 2.46; 95% LOA = from −1.06 to + 1.72 AU). The only study that examined the test‐retest reliability of aquaticity testing protocol has also reported high reliability in the total score of aquaticity test ( r = .993; CV%: 2.04; 95% LOA = 1.06 ± 1.44 AU) in 10 untrained adolescents. In the present study, we also examined the test‐retest reliability of each swimming task of the protocol separately.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, our results showed that the total score of the aquaticity testing protocol is reliable for the evaluation of students’ aquaticity (ICC = 0.98; SEM = 0.54 AU; SEM% = 2.46; 95% LOA = from −1.06 to + 1.72 AU). The only study that examined the test‐retest reliability of aquaticity testing protocol has also reported high reliability in the total score of aquaticity test ( r = .993; CV%: 2.04; 95% LOA = 1.06 ± 1.44 AU) in 10 untrained adolescents. In the present study, we also examined the test‐retest reliability of each swimming task of the protocol separately.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to testing, the participants performed a standardised 10 minutes warm‐up that included 5 minutes of swimming with plank at low intensity and 5 minutes of dynamic stretching exercises in the water. Thereafter, aquaticity was examined using the testing protocol consisting of 10 swimming tasks, as previously described by Varveri et al (Table ). Before the initiation of the testing, the participants underwent 1‐2 familiarisation trials to ensure the proper execution technique for the swimming tasks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations